Analisis Manajemen Keuangan Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat (PAMSIMAS) Desa Tegalsari Barat Dalam Perspektif Ekonomi Syariah (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2022)
Clean water is one of the most vital needs for all humans. Because all community activities in various aspects of life require clean water. According to the National Development Planning Agency (Bappenas) in 2017 the achievement of access to proper drinking water was 84%. And access to proper sanitation is 70.7%. Therefore, in 2007 the Indonesian government formulated all national policies2 to provide clean water and sanitation needs for districts and cities in Indonesia. This program is called PAMSIMAS. The implementation of clean water service activities also needs to pay attention to management principles, because in running an organization it is very necessary to have management, especially in financial management. This study aims to determine the financial management of PAMSIMAS in West Tegalsari Village in a sharia economic perspective. Based on the source obtained, this type of research data includes qualitative or field data (field research) because the researcher wants to explain this research in detail according to the data and facts in the field and the researcher also wants to know in depth about the problems being studied in this research. The results of this study indicate the impact and financial management of PAMSIMAS in West Tegalsari Village. In sharia economics, sharia management includes 3 things, namely clean, responsible and professional.